need help urgently if u want brainliest answer me
q. if x-1/x=3 then find x^3-1/x^3
please answer no spam
Answers
Answered by
6
Given:
= > x - (1/x) = 3.
On cubing both sides, we get
= > (x - 1/x)^3 = (3)^3
![= \ \textgreater \ x^3 - \frac{1}{x^3} - 3 * x * \frac{1}{x} (x - \frac{1}{x} ) = 27 = \ \textgreater \ x^3 - \frac{1}{x^3} - 3 * x * \frac{1}{x} (x - \frac{1}{x} ) = 27](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++x%5E3+-++%5Cfrac%7B1%7D%7Bx%5E3%7D+-+3+%2A+x+%2A++%5Cfrac%7B1%7D%7Bx%7D+%28x+-++%5Cfrac%7B1%7D%7Bx%7D+%29+%3D+27)
![= \ \textgreater \ x^3 - \frac{1}{x^3} - 3(3) = 27 = \ \textgreater \ x^3 - \frac{1}{x^3} - 3(3) = 27](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++x%5E3+-++%5Cfrac%7B1%7D%7Bx%5E3%7D+-+3%283%29+%3D+27)
![= \ \textgreater \ x^3 - \frac{1}{x^3} - 9 = 27 = \ \textgreater \ x^3 - \frac{1}{x^3} - 9 = 27](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++x%5E3+-++%5Cfrac%7B1%7D%7Bx%5E3%7D+-+9+%3D+27)
![= \ \textgreater \ x^3 - \frac{1}{x^3} = 27 + 9 = \ \textgreater \ x^3 - \frac{1}{x^3} = 27 + 9](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++x%5E3+-++%5Cfrac%7B1%7D%7Bx%5E3%7D+%3D+27+%2B+9)
![= \ \textgreater \ x^3 - \frac{1}{x^3} = 36 = \ \textgreater \ x^3 - \frac{1}{x^3} = 36](https://tex.z-dn.net/?f=%3D+%5C+%5Ctextgreater+%5C++x%5E3+-++%5Cfrac%7B1%7D%7Bx%5E3%7D+%3D+36)
Hope it helps!
= > x - (1/x) = 3.
On cubing both sides, we get
= > (x - 1/x)^3 = (3)^3
Hope it helps!
siddhartharao77:
:-)
Similar questions